Draw fashion models! - Hammond, Lee, 1957-. (Cincinnati, Ohio : North Light Books, 1999)
Introduces useful tools and techniques, shows how to portray clothing, fabrics, and hair, and includes demonstrations and practice exercises.
What is fashion illustration? -- Materials -- Basic shapes -- Blending and shading -- Drawing the five basic fabric folds -- Textures and patterns -- Drawing the fashion face -- Drawing fashion hairstyles -- Drawing the hands -- Drawing fashion accessories -- Special effects.
Includes index.
Keywords: Fashion drawing